Level of Pollution of Water from River Rwabakazi Indicated by Metal Ions and Suspended Solids Concentrations. - Habimana, Michael (Kabale University, 2023)
Pollution resulting from increased anthropogenic activities is affecting river Rwabakazi. Its effects are reflected by high concentrations of calcium, iron (II). iron ( 111), magnesium and total suspended solids (TSS). In this study. we report the selected physicochemical parameters of waters of Rwabakazi River and how they varied in the selected study area in kabale district. Globally. 2.l billion people lack access to safely managed drinking water services (WHO/UNICEF. 20I7). Uganda is confronted with over IO million people lacking access to safe drinking water (Ojore, 2019), Kabale Municipality inclusive. The study performed in Kabale university involved titration to determine iron (11), lron (Ill), calcium and magnesium ions; and filtration in determining the amount of suspended solids. The results obtained for the samples showed high concentrations of calcium, magnesium, iron (Il), and iron (Ill) ions and suspended solids as a result of pollution. The concentrations decreased downstream as follows; iron (II) from 60.04 to 54.40 mg/L; iron (Ill) from 19.50 to 16.50 mg/L; calcium from 99.00 to 68.00 mg/L; magnesium from 7 .20 to 6.00 mg/L and TSS from 15.6 to 10.5 mg/Lall of which exceeded the allowed limits by EPA and WHO guidelines for safe water for human use. The available data can be relied on to assert that river Rwabakazi is polluted as a result of erosion and flush flooding but has capacity to undergo natural self-purification although very slowly. Further studies on nutrient and pesticide pollution of this river should be carried out and trees should be planted on slopes of open surfaces to minimize erosion. Keywords: Level, Pollution, Water, River Rwabakazi, Metal Ions, Suspended Solids, Concentrations.